Mindfulness training in swimming: Efforts to reduce burnout and stress in junior athletes - Sukur, A.; Hartono, F. V.; Gani, R. A.; Setiawan, E. (Fizjoterapia polska: Polish Journal of Physiotherapy, 2023)
Purpose. The application of mindfulness training in sports activities showed enhancement, but lack of evidence about the effects of mindfulness associated with burnout and stress in junior swimming athletes through mixed research methods which created a gap in this study. Therefore, this research analyzed the effects of mindfulness on burnout and stress.